Anti-freezing hydrogel and preparation method thereof
By using the synergistic action of zwitterionic polymers and inorganic salts in the hydrogel and combined with the use of glycerol, an anti-freeze hydrogel that is not easy to freeze at low temperatures was prepared, which solved the problem of easy freezing at low temperatures, and achieved efficient anti-freeze and water absorption properties.
Patent Information
- Application Number
- CN202510076968.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-17
AI Technical Summary
Traditional hydrogels are prone to freezing at low temperatures, resulting in degradation of mechanical properties and functional failure. The existing anti-freeze modification strategies have problems with insufficient water absorption performance or risk of freezing.
An anti-frost hydrogel was prepared by adding methacryloylethylsulfobetaine, polyol, crosslinking agent, initiator, etc. to the inorganic salt solution, and performing high-temperature polymerization. This method uses the synergistic effect of zwitterionic polymers and inorganic salts to inhibit the formation of hydrogen bonds between water molecules inside the hydrogel, and forms strong hydrogen bonds with water molecules through glycerol to reduce freezing point.
The prepared anti-freeze hydrogel does not freeze below -70℃, maintains flexibility, and the freezing point is lower than -8℃ after absorbing water. At the same time, the process is simple and the conditions are mild, making it convenient for large-scale production.
Smart Images

Figure HDA0005247383130000011 
Figure HDA0005247383130000012 
Figure HDA0005247383130000013
Abstract
Description
Technical Field
[0001] The invention relates to an improved antifreeze hydrogel and a preparation method thereof, belonging to the technical field of hydrogels. Background Art
[0002] my country's infrastructure transportation projects are gradually expanding to the western plateau areas. However, plateau areas often have the characteristics of low atmospheric pressure, large temperature difference between day and night, and frequent alternation of positive and negative temperatures, which makes concrete buildings extremely vulnerable to high-frequency freeze-thaw damage. Traditional technologies for improving the antifreeze performance of concrete include the use of surface super-hydrophobic coating materials, micro-nano filling densification materials, phase change microcapsule slow-freezing materials, air-entraining agents, etc. However, although the above four materials can improve the antifreeze performance of concrete to varying degrees, the hydrophobic coating is prone to cracking and peeling, and the long-term effectiveness is insufficient. Nanomaterials have strong surface energy, so they are prone to agglomeration when preparing cement-based composite materials. Phase change microcapsules have the problems of low phase change enthalpy, high temperature, and poor thermal conductivity of the capsule wall. The interfacial activity and foam stability of air-entraining agents are weakened in plateau areas, and they are very easy to fail. Therefore, it is urgent to propose a new type of material for improving the antifreeze performance of concrete.
[0003] Hydrogel is a polymer with a three-dimensional network structure and high water content. Due to its good flexibility and biocompatibility, it is widely used in biomedicine, flexible electronic devices and other fields. However, the free water in traditional hydrogels can easily form ice crystals and freeze at zero degrees, causing the hydrogel's mechanical properties to deteriorate and lose functionality. In recent years, researchers have proposed a variety of modification strategies, including the introduction of organic solvents (such as glycerol, ethylene glycol, etc.) and soaking in inorganic salt solutions. Although these methods improve the antifreeze properties of hydrogels, the large-scale introduction of organic solvents will inhibit the hydrogel from absorbing external moisture. Simple soaking will cause the inorganic salt ions to be loosely bound to the water molecules inside the hydrogel. When external moisture invades, there is a risk of leakage, resulting in the antifreeze failure of the hydrogel. Therefore, it is urgent to design a hydrogel that can absorb water and still retain antifreeze properties after absorbing water. Summary of the invention
[0004] Purpose of the invention: In view of the deficiencies of the prior art, the primary purpose of the present invention is to provide an improved antifreeze hydrogel. Another purpose of the present invention is to provide a method for preparing the above-mentioned improved antifreeze hydrogel.
[0005] Technical solution: To solve the above technical problems, the present invention provides a method for preparing an antifreeze hydrogel, comprising the following steps:
[0006] Add methyl acryloyl ethyl sulfobetaine and acrylic acid into the inorganic salt solution and stir evenly, then add polyol, crosslinking agent and initiator in sequence, continue stirring, perform ultrasonic treatment and perform high temperature polymerization reaction to obtain antifreeze hydrogel.
[0007] Furthermore, the inorganic salt is one of lithium chloride, sodium chloride, calcium chloride, zinc chloride and magnesium chloride, preferably lithium chloride.
[0008] Furthermore, the polyol is one of glycerol, ethylene glycol and propylene glycol, preferably glycerol.
[0009] Furthermore, the cross-linking agent is N,N'-methylenebisacrylamide.
[0010] Furthermore, the initiator is one of ammonium persulfate and potassium persulfate, preferably ammonium persulfate.
[0011] Furthermore, the molar ratio of the inorganic salt, methacryloylethyl sulfobetaine, acrylic acid, polyol, crosslinking agent, and initiator is (2.59-23.60): (0.60-7.16): (2.32-27.75): (2.4-13.7): (0.01-0.02): (0.05-0.12).
[0012] Furthermore, the stirring time is continued for more than 15 minutes, and the frequency of the ultrasonic treatment is 100 Hz.
[0013] Furthermore, the temperature of the high temperature polymerization reaction is 60° C., and the high temperature polymerization reaction time is 6 hours.
[0014] The antifreeze hydrogel obtained by the preparation method of the present invention.
[0015] Furthermore, the antifreeze hydrogel of the present invention is in the form of a thin sheet with a thickness of 1 mm to 2.5 mm.
[0016] Furthermore, the antifreeze hydrogel of the present invention will not freeze at a temperature of -70°C, remains flexible, and has a freezing point below -8°C after absorbing water.
[0017] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0018] The present invention first dissolves lithium chloride and polymer monomers in deionized water, then adds a crosslinking agent, and finally adds glycerol and an initiator, and obtains the product through free radical polymerization under high temperature conditions. The zwitterionic polymer methacryloylethyl sulfobetaine provided by the antifreeze hydrogel of the present invention contains hydrophilic sulfonic acid anions and quaternary ammonium salt cations on the molecular chain, which can inhibit the formation of hydrogen bonds between water molecules inside the hydrogel through electrostatic induced hydration, thereby converting freezable weakly bound water into non-freezable strongly bound water, and can also improve the water absorption performance of the hydrogel; on the other hand, directly adding inorganic salts produces an ion hydration effect to tightly bind the water molecules inside the hydrogel, and synergistically uses glycerol to produce strong hydrogen bonds with water molecules, so that the freezing point of the hydrogel is still below -8°C after absorbing water, and the lowest can be below 130°C. The preparation process of the antifreeze hydrogel is simple, the reaction conditions are mild, and it is easy to achieve large-scale production and preparation. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is a differential scanning calorimetry curve of the antifreeze hydrogel prepared in Example 1;
[0020] Figure 2 is a differential scanning calorimetry curve of the antifreeze hydrogel prepared in Example 1 after absorbing water;
[0021] Figure 3 This is a distribution diagram of freezable water / unfrozen water content of the antifreeze hydrogel prepared in Example 1 after absorbing water;
[0022] Figure 4 is a differential scanning calorimetry curve of the antifreeze hydrogel prepared in Example 2 after absorbing water;
[0023] Figure 5 This is a distribution diagram of freezable water / unfrozen water content of the antifreeze hydrogel prepared in Example 2 after absorbing water;
[0024] Figure 6 This is a differential scanning calorimetry curve of the antifreeze hydrogel prepared in Example 3 after absorbing water;
[0025] Figure 7 This is a distribution diagram of freezable water / unfrozen water content of the antifreeze hydrogel prepared in Example 3 after absorbing water;
[0026] Figure 8 This is a differential scanning calorimetry curve of the antifreeze hydrogel prepared in Comparative Example 1 after absorbing water;
[0027] Fig. 9 This is a distribution diagram of freezable water / unfrozen water content of the antifreeze hydrogel prepared in Comparative Example 1 after absorbing water;
[0028] Fig.10 This is a differential scanning calorimetry curve of the antifreeze hydrogel prepared in Comparative Example 2 after absorbing water;
[0029] Fig.11 This is a differential scanning calorimetry curve of the antifreeze hydrogel prepared in Comparative Example 3 after absorbing water. DETAILED DESCRIPTION
[0030] The technical solution of the present invention is further described below in conjunction with embodiments and drawings.
[0031] The specific methods, formulations and instructions used in the following experiments are not intended to limit the present invention.
[0032] Example 1
[0033] Weigh 0.006 mol lithium chloride and stir and dissolve it in 1 ml deionized water to make the lithium chloride concentration in the solution 6.0 mol / L; weigh 0.0042 mol methacryloylethyl sulfobetaine and 0.016 mol acrylic acid and add them to the above lithium chloride solution to make the methacryloylethyl sulfobetaine concentration in the solution 4.2 mol / L and the acrylic acid concentration 16.3 mol / L; then add N,N'-methylenebisacrylamide, glycerol and ammonium persulfate to make the concentration of N,N'-methylenebisacrylamide in the above solution 0.0 2mol / L, the concentration of glycerol was 9.2mol / L, the concentration of ammonium persulfate was 0.12mol / L, the molar ratio of lithium chloride, methacryloylethyl sulfobetaine, acrylic acid, glycerol, N,N'-methylenebisacrylamide, and ammonium persulfate was 6:4.2:16.3:9.2:0.02:0.12. Stir well for 15min, remove bubbles by ultrasound (frequency of 100Hz), transfer the resulting solution into a mold (length×width×height of 40mm×40mm×5mm), and polymerize at 60℃ for 6h to obtain an antifreeze hydrogel.
[0034] The test method of the antifreeze performance of the antifreeze hydrogel in this embodiment is as follows: a differential scanning calorimeter is used to measure the freezing point of the antifreeze hydrogel. A certain amount of hydrogel is placed in an aluminum crucible, and then the sample temperature is reduced from 20°C to -70°C at a rate of 5°C / min. The antifreeze hydrogel sample is kept at -70°C for 10 minutes, and finally heated back to 20°C at 5°C / min. The heat flow during the cooling and heating process is monitored, and the peak value of the heat flow curve during the heating process is the freezing point of the hydrogel. The results are as follows Figure 1 shown.
[0035] The moisture distribution test method of the antifreeze hydrogel in this embodiment is as follows: take an appropriate amount of antifreeze hydrogel in a sample bottle, add water-cement (ordinary Portland cement PO 42.5, the main components are tricalcium silicate, dicalcium silicate, tricalcium aluminate and tetracalcium aluminoferrate) at a ratio of 1:10, stir for 24 hours, and filter the obtained cement filtrate to simulate the invasion of external water, so that the water content of the antifreeze hydrogel increases by 20wt.%. Then seal the sample bottle and let it stand for 12 hours to allow the antifreeze hydrogel to fully absorb water. Use a differential scanning calorimeter to characterize the freezing point and freezable water / unfrozen water content of the antifreeze hydrogel after water absorption. The results are as follows Figure 2 and Figure 3 shown.
[0036] Figure 1 The differential scanning calorimetry curve (heat flow versus temperature curve) of the antifreeze hydrogel prepared in Example 1 is shown in FIG. Figure 1 As shown, in the range of -70°C to 20°C, no obvious endothermic peak appears in the curve, indicating that the antifreeze hydrogel does not undergo phase change during the process, that is, the freezing point of the antifreeze hydrogel is lower than -70°C.
[0037] Figure 2 The differential scanning calorimetry curve (heat flow versus temperature curve) of the antifreeze hydrogel prepared in Example 1 after absorbing water is shown in FIG. Figure 2 As shown, in the range of -30°C to 20°C, there is no obvious endothermic peak in the curve, indicating that the hydrogel does not undergo phase change during the process, that is, the freezing point of the hydrogel is lower than -30°C after absorbing water. Figure 3 It was further confirmed that the freezable water content in the hydrogel was 0.
[0038] Example 2
[0039] The preparation process is the same as that in Example 1, except that the ratio of the raw materials used is different, and the molar ratio of lithium chloride, methacryloylethyl sulfobetaine, acrylic acid, glycerol, N,N'-methylenebisacrylamide, and ammonium persulfate is 6:1.79:6.94:2.74:0.01:0.053, specifically as follows: 0.006 mol of lithium chloride is weighed and dissolved in 1 ml of deionized water, and the concentration of lithium chloride in the solution is 6.0 mol / L; 0.0018 mol of methacryloylethyl sulfobetaine and 0.0069 mol of acrylic acid are weighed and added to the lithium chloride solution, and the concentration of methacryloylethyl sulfobetaine in the solution is 6.0 mol / L; The concentration of acylethyl sulfobetaine is 1.79 mol / L, and the concentration of acrylic acid is 6.94 mol / L; then N,N'-methylenebisacrylamide, glycerol, and ammonium persulfate are added to make the concentration of N,N'-methylenebisacrylamide in the above solution 0.01 mol / L, the concentration of glycerol is 2.74 mol / L, and the concentration of ammonium persulfate is 0.053 mol / L. The mixture is stirred for 15 minutes, and bubbles are removed by ultrasound (frequency is 100 Hz). The resulting solution is transferred into a mold (length × width × height is 40 mm × 40 mm × 5 mm), and polymerized at 60°C for 6 hours to obtain an antifreeze hydrogel.
[0040] The antifreeze performance and water distribution test of the antifreeze hydrogel prepared in this example are as follows: Figure 4 and Figure 5 shown.
[0041] Figure 4 The graph is a relationship between the heat flow and temperature of the antifreeze hydrogel prepared in Example 2 after the hydrogel absorbs water. Figure 4 As shown, the antifreeze hydrogel prepared in this example has an endothermic peak at -11.41°C, and this peak value is the freezing point of the hydrogel after absorbing water.
[0042] Figure 5 This is the distribution diagram of the freezable water and unfrozen water content in the antifreeze hydrogel prepared in Example 2 after absorbing water. Figure 4It can be seen that at -11.41°C, the antifreeze hydrogel prepared in this example has 10.3% freezable water and 59.7% unfrozen water inside the hydrogel after absorbing water, further demonstrating the antifreeze property of the hydrogel.
[0043] Example 3
[0044] The preparation process is the same as that in Example 1, except that the ratio of the raw materials used is different. The molar ratio of lithium chloride, methacryloylethyl sulfobetaine, acrylic acid, glycerol, N,N'-methylenebisacrylamide, and ammonium persulfate is 6:4.2:16.3:2.74:0.02:0.12, specifically as follows: 0.006 mol of lithium chloride is weighed and dissolved in 1 ml of deionized water, and the concentration of lithium chloride in the solution is 6.0 mol / L; 0.0042 mol of methacryloylethyl sulfobetaine and 0.016 mol of acrylic acid are weighed and added to the lithium chloride solution, and the concentration of methacryloylethyl sulfobetaine in the solution is 6.0 mol / L. The concentration of ethyl sulfobetaine is 4.2 mol / L, and the concentration of acrylic acid is 16.3 mol / L; then N,N'-methylenebisacrylamide, glycerol, and ammonium persulfate are added to make the concentration of N,N'-methylenebisacrylamide in the above solution 0.02 mol / L, the concentration of glycerol is 2.74 mol / L, and the concentration of ammonium persulfate is 0.12 mol / L. The mixture is stirred for 15 min, and bubbles are removed by ultrasound (frequency is 100 Hz). The resulting solution is transferred into a mold (length × width × height is 40 mm × 40 mm × 5 mm), and polymerized at 60°C for 6 h to obtain an antifreeze hydrogel.
[0045] The antifreeze performance and water distribution test of the antifreeze hydrogel prepared in this example are as follows: Figure 6 and Figure 7 shown.
[0046] Figure 6 The graph is a relationship between the heat flow and temperature of the antifreeze hydrogel prepared in Example 3 after the hydrogel absorbs water. Figure 6 As shown, the antifreeze hydrogel prepared in this example has an endothermic peak at -9.25°C, and this peak is the freezing point of the hydrogel after absorbing water.
[0047] Figure 7 This is the distribution diagram of the freezable water and unfrozen water content in the antifreeze hydrogel prepared in Example 4 after absorbing water. Figure 6 It can be seen that when the antifreeze hydrogel prepared in this embodiment is at -9.25°C, the freezable water content inside the hydrogel after absorbing water accounts for 10.3%, and the unfrozen water content accounts for 39.7%.
[0048] Comparative Example 1
[0049] The preparation process is the same as that of Example 2, except that glycerol is not used, and the molar ratio of lithium chloride, methacryloylethyl sulfobetaine, acrylic acid, N,N'-methylenebisacrylamide, and ammonium persulfate is 5.9:1.79:6.94:0.01:0.053, specifically as follows: 0.012 mol of lithium chloride is weighed and dissolved in 2 ml of deionized water, so that the concentration of lithium chloride in the solution is 5.9 mol / L; 0.0036 mol of methacryloylethyl sulfobetaine and 0.014 mol of acrylic acid are weighed and added to the above lithium chloride solution, so that the solution is The concentration of methacryloylethyl sulfobetaine is 1.79 mol / L, and the concentration of acrylic acid is 6.94 mol / L; then N,N'-methylenebisacrylamide and ammonium persulfate are added to make the concentration of N,N'-methylenebisacrylamide in the above solution be 0.01 mol / L, and the concentration of ammonium persulfate is 0.053 mol / L. The mixture is stirred for 15 minutes, and bubbles are removed by ultrasound (frequency is 100 Hz). The resulting solution is transferred into a mold (length × width × height is 40 mm × 40 mm × 5 mm), and polymerized at 60°C for 6 hours to obtain an antifreeze hydrogel.
[0050] The antifreeze performance and water distribution test of the antifreeze hydrogel prepared in this comparative example are as follows: Figure 8 and Fig. 9 shown.
[0051] Figure 8 The graph is a relationship between the heat flow and temperature of the antifreeze hydrogel prepared in Comparative Example 1 after the hydrogel absorbs water. Figure 8 As shown, the antifreeze hydrogel prepared in this comparative example has an endothermic peak at -3.73°C, and the peak value is the freezing point of the hydrogel.
[0052] Fig. 9 The distribution diagram of the freezable water and unfrozen water content in the antifreeze hydrogel prepared in ratio 1 after absorbing water. Figure 8 It can be seen that for the antifreeze hydrogel prepared in this comparative example, at -3.73°C, the freezable water content inside the hydrogel after absorbing water accounts for 22.7%, and the unfrozen water content accounts for 47.3%.
[0053] Comparative Example 2
[0054] The preparation process is the same as that of Example 2, except that the method of adding the inorganic salt lithium chloride is different, and the molar ratio of methacryloylethyl sulfobetaine, acrylic acid, N,N'-methylenebisacrylamide, and ammonium persulfate is 1.79:6.94:0.01:0.053, specifically as follows: 0.0036 mol of methacryloylethyl sulfobetaine and 0.014 mol of acrylic acid are weighed and added into deionized water to make the concentration of methacryloylethyl sulfobetaine in the solution be 1.79 mol / L , the acrylic acid concentration is 6.94 mol / L; then N,N'-methylenebisacrylamide and ammonium persulfate are added to make the concentration of N,N'-methylenebisacrylamide in the above solution 0.01 mol / L, and the concentration of ammonium persulfate is 0.053 mol / L, and the mixture is stirred for 15 minutes, and the bubbles are removed by ultrasound (frequency is 100 Hz), and the obtained solution is transferred into a mold (length × width × height is 40 mm × 40 mm × 5 mm), and polymerized at 60°C for 6 hours to obtain a hydrogel. The obtained hydrogel is immersed in a 20wt.% lithium chloride solution for 48 hours until the swelling equilibrium is reached, and the hydrogel is obtained.
[0055] The antifreeze performance and water distribution test of the antifreeze hydrogel prepared in this comparative example are as follows: Fig.10 shown.
[0056] Fig.10 The curve diagram of the relationship between the heat flow and temperature of the hydrogel prepared in Comparative Example 2 after the hydrogel absorbs water is shown in FIG. Fig.10 It can be seen that the freezing point of the hydrogel after absorbing water is 12.78°C.
[0057] Comparative Example 3
[0058] Referring to the prior art HOU LX, JU H, HAO XP, et al. Intrinsic Anti-Freezing and Unique Phosphorescence of Glassy Hydrogels with Ultrahigh Stiffness and Toughness at Low Temperatures [J]. Advanced Materials, 2023, 35 (21), the specific process is as follows: weigh 0.018 mol acrylamide and 0.042 mol methacrylic acid and add them into deionized water so that the concentration of acrylamide in the solution is 3.6 mol / L and the concentration of methacrylic acid is 8.4 mol / L; then add potassium persulfate so that the concentration of potassium persulfate in the above solution is 0.059 mol / L, and finally add 10 μL tetramethylethylenediamine, stir well, remove bubbles by ultrasound, transfer the resulting solution into a mold, and polymerize at 45°C for 6 hours to obtain a hydrogel.
[0059] The antifreeze performance and water distribution test of the antifreeze hydrogel prepared in this comparative example are as follows: Fig.11 shown.
[0060] Fig.11 This is the relationship curve between the heat flow and temperature of the hydrogel after the hydrogel absorbs water in Comparative Example 3. It can be seen that the freezing point of the hydrogel after absorbing water is 5.18°C.
[0061] The above embodiments are only used to illustrate the technical solutions of the present invention, but the implementation methods of the present invention are not limited to the above embodiments. Any other modifications, substitutions, and combinations that do not deviate from the essence and principles of the present invention should be equivalent replacement methods without departing from the purpose of the present invention and are included in the protection scope of the present invention.
Claims
1. A method for preparing an antifreeze hydrogel, characterized in that: The following steps are involved: Add methacryloylethyl sulfobetaine and acrylic acid into the inorganic salt solution and stir evenly, add polyol, crosslinking agent and initiator, continue stirring, perform ultrasonic treatment and perform high temperature polymerization reaction to obtain antifreeze hydrogel.
2. The method for preparing the antifreeze hydrogel according to claim 1, characterized in that: The inorganic salt is one of lithium chloride, sodium chloride, calcium chloride, zinc chloride and magnesium chloride.
3. The method for preparing the antifreeze hydrogel according to claim 1, characterized in that: The polyol is one of glycerol, ethylene glycol and propylene glycol.
4. The method for preparing the antifreeze hydrogel according to claim 1, characterized in that: The crosslinking agent is N,N'-methylenebisacrylamide.
5. The method for preparing the antifreeze hydrogel according to claim 1, characterized in that: The initiator is one of ammonium persulfate and potassium persulfate.
6. The method for preparing the antifreeze hydrogel according to claim 1, characterized in that: The molar ratio of inorganic salt, methacryloylethyl sulfobetaine, acrylic acid, polyol, crosslinking agent and initiator is (2.59-23.60): (0.60-7.16): (2.32-27.75): (2.4-13.7): (0.01-0.02): (0.05-0.12).
7. The method for preparing the antifreeze hydrogel according to claim 1, characterized in that: The stirring time is continued for more than 15 minutes, and the frequency of ultrasonic treatment is below 100 Hz.
8. The method for preparing the antifreeze hydrogel according to claim 1, characterized in that: The temperature of the high temperature polymerization reaction is 45°C-60°C, and the high temperature polymerization reaction time is 6h-12h.
9. The antifreeze hydrogel obtained by the preparation method according to any one of claims 1 to 8.
10. The antifreeze hydrogel according to claim 9, characterized in that: The antifreeze hydrogel is in the form of a thin sheet with a thickness of 1mm-2.5mm. It will not freeze at a temperature of -70°C, remains flexible, and has a freezing point below -8°C after absorbing water.
Citation Information
Patent Citations
Antifreeze hydrogel as well as preparation method and application thereof
CN110760152A
Zwitterionic anti-freezing organic hydrogel as well as preparation method and application thereof
CN113549173A
Anti-freezing and conductive organic hydrogel as well as preparation method and application thereof
CN114276500A
Preparation and application of monoproton conductive anti-freezing organic hydrogel electrolyte
CN116284851A
Preparation method and application of multifunctional hydrogel electrolyte material
CN117700618A